Clinical simulation strategies for knowledge integration relating to initial critical recognition and management of COVID-19 for use within continuing education and health- related academia in Brazil: a descriptive study - Brandão, Carolina Felipe Soares (2020)
BACKGROUND: The COVID-19 pandemic has led to an immense need to develop training on case recgnition and management, with a focus on patients’ and health professionals’ safety at several levels of healthcare settings in Brazil. Different simulation strategies can be included in the diverse clinical care phases for these patients. OBJECTIVE: To suggest a complete simulation-based training program for Brazilian hospitals and/or academic institutions at this moment of the pandemic. DESIGN AND SETTING: Descriptive analysis on possible simulated clinical cases using different methodologies, thereby supporting suspected or confirmed COVID-19 patients. METHODS: This was a reflective theoretical descriptive study on an educational program based on clinical simulation, with four practical phases at different performance and complexity levels. Wearing, handling and adequately disposing of personal protective equipment, along with specific respiratory procedures in different healthcare settings up to intensive care for seriously infected patients were addressed. RESULTS: This program was designed for application at different Brazilian healthcare levels through different clinical simulation strategies. Summaries of expected performance were suggested in order to standardize technical capacity within these simulation settings, so as to serve these levels. CONCLUSIONS: Developing training programs for situations such as the current COVID-19 pandemic promotes safety not only for patients but also for healthcare workers. In the present context, clear definition of which patients need hospital outpatient or inpatient care will avoid collapse of the Brazilian healthcare system. Institutions that do not have simulated environments can, through the examples described, adopt procedures to promote didactic information in order to help healthcare professionals during this time.